Rancang Bangun Panel Instalasi Listrik dengan Prinsip Engineering Safety Ruang Spray Booth Pengecatan Bodi Kendaraan - Aldi Zulkarnain Hasibuan; Donny Fernandez; Andrizal Andrizal; Nuzul Hidayat (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
This study aims to design and develop an electrical installation panel by applying engineering safety principles in the water spray booth of a vehicle body painting system. Field observations indicate that electrical panels in painting rooms often do not meet safety standards, which can lead to short circuits and potential fire hazards. The research employed a Research and Development (R&D) method using a simplified Borg and Gall model consisting of nine stages, starting from problem identification to effectiveness testing. Expert validation results obtained a score of 87.5% (highly valid), practicality testing yielded 90% (very practical), and effectiveness tests showed an average current of 4.1 A, with both the MCB and emergency stop functioning optimally. The developed panel product is declared feasible to be used as a practical learning media for automotive electrical systems. Based on the test results, the panel product was declared suitable for use and can be used as a learning medium in automotive electrical practice, helping to increase understanding of the application of safety in electrical installations in the automotive industry.